Emili Samper, ed. (2016), «The Myths of the Republic: Literature and Identity», Kassel, Edition Reichenberger, 242 pp. - Llombart Huesca, Maria (Caplletra. Revista Internacional de Filologia, 2019)
Ressenya sobre el llibre d'Emili Samper, ed. (2016), The Myths of the Republic: Literature and Identity, Kassel, Edition Reichenberger, 242 pp., ISBN 978-3-944244-53-2.